1989
DOI: 10.2134/jpa1989.0103
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Soil Nitrate Concentrations in Late Spring and Corn Yields in Iowa

Abstract: A soil test for improving N management is greatly needed in much of the Corn Belt. Relationships between yields of corn (Zea mays L.) grain and concentrations of nitrate in the surface l‐ft layer of soils when corn plants were 6 to 12 in. tall were studied across a total of 756 plots at several locations during 1985 and 1986 to evaluate the late‐spring soil test for nitrate. The time of sampling for this soil test represents a compromise between the need to sample late enough to reflect the effects of spring w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
172
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(193 citation statements)
references
References 6 publications
11
172
2
8
Order By: Relevance
“…Among the various major nutrients required for proper plants, Nitrogen has a key role and particularly it has been proven for maize by various experiments (Subramanian et al, 2006;Carpici et al, 2010). The nitrogen requirement of maize is depend on weather conditions, soil type and crop rotation pattern (Blackmer, et al, 2009;Bundy, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various major nutrients required for proper plants, Nitrogen has a key role and particularly it has been proven for maize by various experiments (Subramanian et al, 2006;Carpici et al, 2010). The nitrogen requirement of maize is depend on weather conditions, soil type and crop rotation pattern (Blackmer, et al, 2009;Bundy, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Critical concentrations generally were lower than those observed by Binford et al (1992a) and Blackmer et al (1989). The mean critical levels for NO'g to 30 cm, for example, were 19 mg N kg'^ in the present study, 29 mg N kg"^ in the study reported by Binford et al (1992a), and 25 mg N kg'^ in the study reported by Blackmer et al (1989).…”
Section: Methodscontrasting
confidence: 63%
“…1 and 2, this method of identifying critical levels has two major shortcomings. The first, as noted by Blackmer et al (1989), is that the determined value for critical concentration varies with the model used. The second, as noted …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The late spring nitrate test (LSNT) is based on the measurement of nitrate-N concentration in the 30 cm surface layer of soil when the plants are 15-30 cm tall. This test has shown reasonably good correlations with yield response to N fertilization (Magdoff et al, 1984 andBlackmer et al, 1989;Fox et al, 1989;Binford et al, 1992;Bundy et al, 1999). Use of the LSNT also has been a useful tool to reduce nitrate loss to water resources.…”
Section: Chapter 3 Effects Of Crop Rotation and Nitrogen Fertilizatimentioning
confidence: 97%